Induction of a tumor-metastasis-receptive microenvironment as an unwanted and underestimated side effect of treatment by chemotherapy or radiotherapy - Ratajczak, Mariusz Z (BioMed Central, 2013)
There are well-known side effects of chemotherapy and radiotherapy that are mainly related to the toxicity and impaired function of vital organs; however, the induction by these therapies of expression of several pro-metastatic factors in various tissues and organs that in toto create a pro-metastatic microenvironment is still, surprisingly, not widely acknowledged. In this review, we support the novel concept that toxic damage in various organs leads to upregulation in “bystander” tissues of several factors such as chemokines, growth factors, alarmines, and bioactive phosphosphingolipids, which attract circulating normal stem cells for regeneration but unfortunately also provide chemotactic signals to cancer cells that survived the initial treatment. We propose that this mechanism plays an important role in the metastasis of cancer cells to organs such as bones, lungs, and liver, which are highly susceptible to chemotherapeutic agents as well as ionizing irradiation. This problem indicates the need to develop efficient anti-metastatic drugs that will work in combination with, or follow, standard therapies in order to prevent the possibility of therapy-induced spread of tumor cells.